STRATEGI PENGEMBANGAN ATRAKSI WISATA BUDAYA DI KAWASAN SARIBU RUMAH GADANG KANAGARIAN KOTO BARU KABUPATEN SOLOK SELATAN - Fajri, Muhammad; Kasmita, Kasmita; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2017)
This research starts from the observation that researcher did in theKawasan Saribu Rumah Gadang that the area is a center of culture that exists inSouth Solok Regency. But the researchers found a lack of awareness of preservingthe culture indicated by the surrounding communities. Problems that researchersfound is tourists do not recognize about the existence of tourist attractions in thearea, tourists visiting only for Selfie and a lot of the attitude shown by thecommunity as indifferent existence. The purpose of this study is to describe howthe development strategy of cultural tourism attractions in the Kawasan SaribuRumah Gadang Kanagarian Koto Baru South Solok Regency.Type of this research is a descriptive qualitative research. The populationin this research is a community was lived in the area either custom or communityleaders who have no status in the community. Sampling technique was PurposiveSampling by viewing of Something to See, Something to Buy, Something to Do.The number of samples in this study was 7 people. The technique of datacollection is done by direct communication through interviews, observation anddocumentation. Furthermore the data analyzed, reduced and drawn conclusions.The results of this research can be concluded among others: Internalfactors being the weakness of the Cultural Attractions in the Kawasan SaribuRumah Gadang: a)Lack of organized cultural event, such as the creation of the oldcustoms of the food to be a huge cost disadvantage at every event, b) lack ofregeneration of connector/successor customs evolved into one of the factors whichweaken us in expanding it. External factors that become a cultural touristattraction Opportunities in the Kawasan Saribu Rumah Gadang is: a) the existingart workshops in the area of Koto Baru can be one opportunity to enliven anypickles that are in the area, b) Roles and the Government can help in this customevent in funding. External factors become a threat in the area's CulturalAttractions Saribu Rumah Gadang is: a) not many adolescents who want to carryon and preserve the custom events that are in the Kawasan Saribu Rumah Gadang,b) generation special food maker also belongs a little in the Kawasan SaribuRumah Gadang.Keywords: Strategy, Tourist Attractions, Culture, Kawasan Saribu RumahGadang, Kanagarian Koto Baru, South Solok Regency